Using environmental niche modelling for investigating the modes of speciation and the impact of global climate change on the distribution of the new world Myotis bats - Akdoğan, Ece. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
According to recent data, an extinction event takes place in every 20 minutes inferentially, and it is estimated that the sixth mass extinction might already be happening with climate change being argued to be one of the prominent reasons. Effective and comprehensive conservation methods must be applied in order to prevent or decrease the levels of the aforementioned extinction. The predictions regarding how species distribution and abundance is affected by climate patterns play a significant role to realize conservation goals and protect the ecosystems. The same modelling approaches that are used to predict changes in species distributions in the future, due to climate change, can also be used to try to understand modes of speciation in a historical perspective of the past. The results of this study demonstrate that the 25 out of 26 New World Myotis species investigated in this study will experience range losses in the face of climate change by 2070. The results also show that the main mode of speciation in the New World bat genus Myotis was primarily allopatric, coupled with significant niche divergences. Predominantly allopatric distributions were observed for most sister species groups (four/five), and for some of the deeper nodes in the phylogeny.
Keywords: Bats -- Climatic factors.; Myotis -- Climatic factors.